What is the best first‐line antibiotic for uncomplicated UTI in women?. Issue 10 (October 2017) - Dwivedi, Roli; Ofstedal, Joseph
Abstract : EVIDENCE‐BASED ANSWER : Nitrofurantoin, trimethoprim/sulfamethoxazole (TMPSMX), and fluoroquinolone antibiotics are essentially of equivalent efficacy (SOR: A, meta‐analyses of RCTs) for uncomplicated cystitis in women. Nitrofurantoin has few adverse events and minimal resistance currently and is recommended as a first‐line antibiotic (SOR: C, expert opinion).